Integral development program of rural zone Gulf of Nicoya: Achievements and experiences - Pacheco-Urpí, Oscar (2016)
The objective of this paper is to show the achievements and experiences developed in the Program, through the management, to diversify the production and generation of employment, the management of natural resources and education, and training for a culture of change. In the viewed, the problem as the lack of a vision to allow a comprehensive resolution of the problems. To do this, it has been applying the methodology implemented in rural development projects with influence of the Leader method +, with joint actions, continuous and planned with the organizations. The work carried out has led the entire organizational base, for example, on the island of Chira, has enabled foster the basis for the development of oyster farming in the Gulf of Nicoya, there has been a significant management for the implementation of good practices for the use of natural resources through supporting the development and strengthening of the organizations related to the areas of responsible fishing and the integral management systems of waste. It has also been the role that it has complied with the Program of the Gulf in the management and routing of the trainings for the strengthening of the organizations served and for the learning of the inhabitants of the coastal communities of the Gulf.